Dendritic cell-derived exosomes as anti-cancer cell-free agents: new insights into enhancing immunogenic effects - Redkin, Tikhon; Turubanova, Victoria (Frontiers in Immunology, 2025)
The secretome of immune cells is currently a major focus in both diagnostic and therapeutic contexts. Cell-free therapeutic agents attract even more attention in cancer immunotherapy research, as their properties are comparable to, and sometimes surpass, those of cell-based immunotherapy. This is particularly evident when dendritic cell-based vaccines are compared with dendritic cell-derived exosomes (dexosomes). However, there is still significant potential for further research and optimization. We propose incorporating immunogenic cell death stimuli into the production of dendritic cell-derived exosomes in order to improve their effectiveness as a cell-free anti-cancer treatment. In this review, we suggest a new strategy to enhance the immunogenic potential of dexosomes, as well as summarize and compare immunogenic proprieties of dendritic cells and dendritic cells-derived exosomes as anti-cancer agents.